The Effect of the E5 Learning Cycle Model with Snakes and Ladders Game on Students’ Cooperation: * - Ni Made Rai Sri Dewi; I Gusti Agung Ayu Wulandari; I Gede Astawan (Universitas Pendidikan Ganesha, 2025)
Cooperation trains children to interact positively, respect others, and understand that collective success is more important than individual achievement alone. Nowadays, the decline of students’ cooperative character has become a major challenge for teachers. This study aims to analyze the effect of the 5E Learning Cycle model assisted by the Snakes and Ladders game on students’ cooperative character in social studies learning for fourth-grade elementary school students. The study employed a quasi-experimental design with a non-equivalent control group design. The population consisted of 282 students, and through cluster random sampling, 32 students were assigned respectively to the experimental group and the control group. Data were collected using a four-point scale questionnaire and analyzed with a t-test. The results showed that the experimental group had an average post-test score of 89.80% (high category), while the control group had 69.06% (moderate category). The t-test produced tcount = 15.743 > ttable = 1.999, indicating that H0 was rejected and H1 was accepted. Thus, the 5E Learning Cycle model assisted by the Snakes and Ladders game had a significant effect on students’ cooperative character in social studies learning. The implication of this study is that it can serve as a reference for innovative learning strategies that encourage active student engagement while instilling social values relevant to the Pancasila Student Profile.